The Meaning of the Poem Sumbawa Horse by Dinullah Rayes: A Review of Riffaterre's Semiotics - Diana, Jumianti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to express the meaning of horses for the people of Sumbawa through the poem "Kuda Sumbawa" by Dinullah Rayes. The research method used is descriptive qualitative method using semiotic theory approach. Data collection was done with library, listening and note-taking techniques. The data analysis was carried out using the semiotic model reading method consisting of heuristic and hermeneutic or retroactive reading. The results show that horses owned by the Sumbawa people have two categories, namely ordinary pet horses as riding horses that are released to graze in the open fields and race horses whose stables are placed near the owner's house with very good care. Race horses are priced differently from ordinary horses. It is usually ridden by a child jockey without using a saddle. The poem describes the owner of a famous race horse who is still friendly to others.